Sucessful use of lysozymes in the treatment of endometritis - SADASIVARAO, K; RAJU, K G SOLMON; PRASAD, CH RAVINDRA (The Indian Journal of Animal Reproduction, 2023)
The enzyme lysozyme was successfully used for the treatment of bacterial endometritis in buffalo.